DINAMIKA IIUBUNGAN AUSTRALIA ASIA TIMUR (1997 2005) - Adriana Elisabeth (Jurnal Penelitian Politik, 2007)
In this summary, Australia East Asian relations cover Australia bilateral, regional and multilateral relations with Cina Indonesia Japan and Singapore during 1997-2005. In this regard, there are five strategic issues, which have impacts to these relations. They are trade and investment, energy security, international migration, bioterrorism. and border issues. Australia-East Asian relations is also affected by the Asian Crisis in 1997, and domestic political conditions in individual East Asian countries, particularly Indonesia.